Auto-Bäcklund Transformation for Fifth Order Equation of the Burgers Hierarchy - İnan, İbrahim Enam (My University, 2019)
In this paper, we implemented Auto-Bäcklund transformation for fifth order equation of the Burgershierarchy. Auto-Bäcklund transformation was developed as a direct and simple method to obtainsolutions of nonlinear partial differential equations by Fan.
Keywords: Matematik